2001
DOI: 10.1108/09684880110381292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and the invisible student: theories, practice and problems in evaluating distance education provision

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…It has been found that problems such as lack of direct feedback, active participation, communication and interaction in distance education environments have been expressed by instructors in different studies (Shaytura et al, 2020;Fojtík, 2018;Watts, 2016;Zhao et al, 2005). It is also supported by the studies in the literature that it affects the teaching staff negatively and creates a negative perception towards distance education (Gunawardena & McIsaac, 2013;Bernard et al, 2020;Larreamendy-Joerns & Leinhardt, 2006;Gilroy et al, 2001). When the findings of the research were examined, it was concluded that the instructors perceived technical problems such as connection and technological infrastructure and instructional problems such as motivation, participation, communication, student follow-up, feedback and evaluation as very important in the distance education model.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…It has been found that problems such as lack of direct feedback, active participation, communication and interaction in distance education environments have been expressed by instructors in different studies (Shaytura et al, 2020;Fojtík, 2018;Watts, 2016;Zhao et al, 2005). It is also supported by the studies in the literature that it affects the teaching staff negatively and creates a negative perception towards distance education (Gunawardena & McIsaac, 2013;Bernard et al, 2020;Larreamendy-Joerns & Leinhardt, 2006;Gilroy et al, 2001). When the findings of the research were examined, it was concluded that the instructors perceived technical problems such as connection and technological infrastructure and instructional problems such as motivation, participation, communication, student follow-up, feedback and evaluation as very important in the distance education model.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…In the early 1990s, in response to Commonwealth Government initiatives relating to the quality of university education, the University had a need to design a suitable system to ensure the quality of all its educational programmes. We will not delve too far here into what might be meant by educational quality (Vidovich, Fourie et al 2000;Gilroy, Long et al 2001), except to say that it was seen to relate to ensuring that course documentation reflected practice and assisted in the improvement of practice. In late 1993 Bowden was given the task of going around the University to speak about the need to introduce some sort of EQA system, and to discuss how this might be done.…”
Section: How the University Adopted Its System Of Programme Quality Amentioning
confidence: 99%
“…Nas duas últimas décadas tem crescido o debate e a preocupação com o desempenho de instituições educacionais no contexto internacional, especialmente, quando muitos governos iniciam um processo de desregulamentação dos cursos de graduação e pós-graduação e quando há um considerável aumento na oferta desses cursos à distância (Gilroy et al, 2001;Pounder, 1999;Martens e Prosser, 1998;Varey, 1993).…”
Section: Introductionunclassified